ANALISIS PENERAPAN KEBIJAKAN PROGRAM GEMBIRA DESA TERHADAP RENCANA PEMBANGUNAN DESA DIKECAMATAN KABAENA SELATAN KABUPATEN BOMBANA (Studi Kasus : Desa Batuawu, Langkema, Ponunu dan Pongkalaero) - Ikhfa Yunisa; M. Nastis; Manat Rahim (Universitas Halu Oleo, 2019)
This study analyzes the management of the Village Joy Program in Kabaena Selatan District,Bombana Regency, based on the application of its functions in the process and stages of activities includingplanning, organizing, actuating, leading, coordinating , Commanding and Motivation (monitoring), andcontrolling (controlling), as well as the management of Gembira Desa funds for the 3 main components ofthe Gembira Desa program include: (1) infrastructure program activities; (2) Development of economic,socio-cultural activities; (3) Strengthening apparatus and community services. This research uses qualitativeresearch design, data collection techniques used are document studies, interviews and direct observation.The research informants were determined by the snowball sampling technique, including technical actors atthe district level, actors in the sub-district, village actors, community institutions and community groups. Theresults showed that (1) The management of the village's happy program had not gone well, where theGembira Desa program managers had not yet coordinated with each other, especially in the management offunds that were not transparent, so that good communication was needed so that the program officials andmanagers could run according to what is expected and the outcome of the village happy program outcomecan be achieved; (2) Management of the Gembira Desa program budget is seen in terms of allocation andrealization of funds, the program of activities has been carried out 100%, both infrastructure developmentactivities, economic, social and cultural development and, strengthening apparatus and community services.In terms of long-term benefit principles, the management of village happy funds is still far from expectations.Keywords: Program Management, Gembira Desa